Do we measure what we get? - Jennifer Kunz (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2008)
Performance measures shall enhance the performance of companies by directing the attention of decision makers towards the achievement of organizational goals. Therefore, goal congruence is regarded in literature as a major factor in the quality of such measures. As reality is affected by many variables, in practice one has tried to achieve a high degree of goal congruence by incorporating an increasing number of these variables into performance measures. However, a goal congruent measure does not lead automatically to superior decisions, because decision makers' restricted cognitive abilities can counteract the intended effects. This paper addresses the interplay between goal congruence and complexity of performance measures considering cognitively-restricted decision makers. Two types of decision quality are derived which allow a differentiated view on the influence of this interplay on decision quality and learning. The simulation experiments based on this differentiation provide results which allow a critical reflection on costs and benefits of goal congruence and the assumptions regarding the goal congruence of incentive systems.
Keywords: M10; M41; 330; Performance measurement; goal congruence; experience-based learning; simulation-based research; Performance Measurement; Betriebswirtschaftliches Ziel; Lernprozess